Effect of strength and power training on tackling ability in semiprofessional rugby league players - Speranza, M. J. A.; Gabbett, T. J.; Johnston, R. D.; Sheppard, J. M. (The Journal of Strength and Conditioning Research, 2016)
This study examined the influence of a strength and power program on tackling ability in rugby league players. Twenty-four semiprofessional rugby league players (mean ± SD age, 23.4 ± 3.1 years) underwent tests of upper-body strength (3 repetition maximum [RM] bench press), lower-body strength (3RM squat), upper-body power (plyometric push-up), and lower-body power (countermovement jump [CMJ]). Muscular strength relative to body mass was also calculated. Tackling ability of the players was assessed using video analysis of a standardized one-on-one tackling drill. The players then underwent 8 weeks of strength and power training as part of their preseason training before being retested. Training resulted in significant (p = 0.01) improvements in absolute and relative measures of squat, bench press, CMJ peak power, and plyometric push-up peak power. The strongest correlates of change in tackling ability were changes in 3RM squat (r = 0.60; p < 0.01) and squat relative to body mass (r = 0.54; p < 0.01). The players with the greatest improvements in 3RM squat and squat relative to body mass (i.e., responders) had significantly greater improvements in tackling ability than nonresponding players (p = 0.04; effect size [ES] = 0.85). A small, nonsignificant difference (p = 0.20; ES = 0.56) in tackling ability was found between responders and nonresponders for lower-body power. The findings of this study demonstrate that the enhancement of lower-body muscular strength, and to a lesser extent muscular power, contribute to improvements in tackling ability in semiprofessional rugby league players.